Peningkatan Kognitif Anak Melalui Kegiatan Bermain Warna Menggunakan Kertas Origami Pada Anak Usia Dini - Affrita Destri Murni; Asnawati Asnawati; Dwi Nomi Pura (Early Childhood Research and Practice, 2026)
The ability to recognize colors is a crucial component of early childhood cognitive development. At this stage, color recognition is part of a learning process that fosters cognitive thinking and memory, thereby supporting overall cognitive growth. Early childhood color recognition encompasses three specific aspects: correctly naming, pointing to, and categorizing colors. The researcher addressed these skills through Classroom Action Research aimed at enhancing color recognition in children aged 3–4 years via color-based play activities using origami paper at PAUD Cita Ananda in Central Bengkulu. This study is intended to serve as a reference for educational institutions, teachers, and early childhood educators in selecting appropriate teaching methods and media to stimulate cognitive development in alignment with children's developmental stages. The study employed a Classroom Action Research (CAR) methodology with a quantitative descriptive approach, conducted over two cycles. Each cycle comprised stages of planning, action implementation, observation, and reflection, and spanned two face-to-face sessions. A cycle was repeated if learning outcomes failed to meet the established mastery indicators. The results demonstrated a significant improvement in color recognition abilities among children aged 3–4 years. The achievement rate was 60% in Cycle I and rose to 92% in Cycle II, representing a 32% increase. These findings indicate that color-based play activities utilizing origami are effective in optimally enhancing color recognition skills in accordance with early childhood developmental stages.